KAIDAH PELESAPAN DALAM KONSTRUKSI KALIMAT MAJEMUK BAHASA INDONESIA - Setiawan, Teguh (LITERA, 2005)
This research study aims to describe the rules of ellipsis in compound and complex sentences. The sources of the data were two newspapers, Kompas and Kedaulatan Rakyat, the edition of March 2002. The data were collected by using observation and recording techniques. They were then analyzed by the substitution method. On the basis of this method, the omission and substitution techniques were employed. Based on the analysis of the findings, the subject, predicate and object ellipsis can be found in compound sentences and the subject ellipsis in complex sentences. The rules of ellipsis in compound sentences are that (1) the omission can be done if the omitted element is the same; (2) the omission of the subject and predicate is always made in the clause after the coordinative conjunction and the omission of the object is made in the clause before the coordinative conjunction; (3) the referential characteristic of the omitted element is always anaphoric. The rules of ellipsis in complex sentences are that (1) the omitted element must be the same; (2) the omitted element is in the clause preceded by a subordinative conjunction or the dependent clause; (3) the referential characteristic of the omitted element is cataphoric or anaphoric.